Avaliação do transplante de células-tronco precursoras de neurônios inibitórios na amígdala basolateral em camundongos tratados com cocaína na ansiedade e na preferência condicionada por lugar e suas correlações neurobiológicas - Yokoyama, Thais Suemi [UNIFESP] (2017)
Drug addiction is one of the main problems modern society, as it can affect several areas of society, economy and public health. Studies have shown that in addition to the pharmacological effects of drugs of abuse, the environmental context where the individual makes use of it is extremely important for the development of dependence on the substance with potential for abuse. Moreover, they showed the important involvement of the basolateral amygdala by promoting desire for the use of the drug only by exposure to environments previously associated with such use. In order to better understand this pathology, we used stem cell transplantation, an inhibitory interneuron from the medial ganglionic eminence (EGM), to modulate pathways related to chemical dependence and to analyze possible behavioral changes. Thus, our objective was to evaluate the effects of stem cell transplantation of inhibitory interneuron on anxiety behaviors, preference conditioned by cocaine-induced site and characterize possible neuroanatomic structures involved in the conditioned response. For this, we used GFP + mice to obtain EGM stem cells and the hosts were Swiss mice at 2 months of age. After 30 days of cell transplantation, the animals were exposed to the high cross labyrinth for anxiety analysis, the next day the animals were conditioned to cocaine and submitted to the postconditioning test to evaluate the preference conditioned by place. Our results showed that inhibitory precursor cell transplantation was not able to alter anxiety behavior, but it potentiated cocaine- induced preference. In relation to the expression of c-fos, we evaluated the basolateral amygdala, medial prefrontal cortex, tegmental ventral area, nucleus accumbens (core and shell) and dorsal striatum. The expression of c-fos in the structures evaluated was not altered by the presence of EGM cells, only a pharmacological alteration of cocaine. Taken together, our results suggest that neural precursor transplantation from EGM is not capable of altering anxiety behavior, but has influenced cocaine-induced site-based preference